Dystrophin muscle enhancer 1 is implicated in the activation of non-muscle isoforms in the skeletal muscle of patients with X-linked dilated cardiomyopathy. - Bastianutto, C; Bestard, J; Lahnakoski, K; Broere, D; De Visser, M; Zaccolo, M; Pozzan, T; Ferlini, A; Muntoni, F; Patarnello, T; Klamut, H (2001)
X-linked dilated cardiomyopathy (XLDC) is a dystrophinopathy characterized by severe cardiomyopathy with no skeletal muscle involvement. Several XLDC patients have been described with mutations that abolish dystrophin muscle (M) isoform expression. The absence of skeletal muscle degeneration normally associated with loss of dystrophin function was shown to be due to increased expression of brain (B) and cerebellar Purkinje (CP) isoforms of the gene exclusively in the skeletal muscle of these patients. This suggested that the B and CP promoters have an inherent capacity to function in skeletal muscle or that they are up-regulated by a skeletal muscle-specific enhancer unaffected by the mutations in these patients. In this work we have analyzed the deletion breakpoints of two XLDC patients with deletions removing the M promoter and exon 1, but not affecting the B and CP promoters. Despite the presence of several muscle-specific regulatory motifs, the B and CP promoters were found to be essentially inactive in muscle cell lines and primary cultures. As dystrophin muscle enhancer 1 (DME1), the only known muscle-specific enhancer within the dystrophin gene, is preserved in these patients, we tested its ability to up-regulate the B and CP promoters in muscle cells. B and CP promoter activity was significantly increased in the presence of DME1, and more importantly, activation was observed exclusively in cells presenting a skeletal muscle phenotype. These results point to a role for DME1 in the induction of B and CP isoform expression in the skeletal muscle of XLDC patients defective for M isoform expression.